Analysis of the Role of Validation and Verification of Socio-Economic and Household Data on the Quality of the Results of the 2026 National Socio-Economic Survey (SUSENAS) at the Central Statistics Agency of Mandailing Natal Regency - Jureid Jureid; Rizky Auliya Nasution; Risna Hayati; Riski Rahmadani; Rayhan Jhonson; Rahmat Firdaus; Riswandi MTD (Jurnal Pengabdian Nusantara, 2026)
This study aims to analyze the role of validation and verification of socioeconomic and household data on the quality of the 2026 National Socioeconomic Survey (SUSENAS) results at the Central Bureau of Statistics of Mandailing Natal Regency. The study used a qualitative approach with a case study design. Data were obtained through in-depth interviews with key informants involved in the SUSENAS implementation, observations of the quality control process, and a review of guideline documents and survey implementation reports. Data analysis was conducted through data reduction, data presentation, and thematic conclusion drawing using triangulation techniques to ensure the validity of the findings. The results show that validation acts as an initial screening mechanism to ensure the completeness, consistency, and logical fairness of data through automated systems and manual checks. Meanwhile, verification serves as a confirmation stage through rechecking and clarification of key variables. Both processes contribute significantly to improving the accuracy, consistency, reliability, and credibility of the SUSENAS results. The effectiveness of validation and verification is influenced by human resource competency, technological support, internal coordination, and the geographic conditions of the work area. This study confirms that strengthening quality control mechanisms is a strategic factor in ensuring the quality of socioeconomic statistics at the regional level.